Prevalence and associated factors of self-reported oral health problems among adults in the Fanteakwa districts in Ghana - Joana Kwabena-Adade; Enoch Aninagyei; Joy Ato Nyarko (BMC Oral Health, 2025)
Abstract Background There is a paucity of data on oral health problems among the residents of Fanteakwa districts (South and North) in the Eastern region of Ghana. Therefore, this study assessed the prevalence and factors associated with self-reported oral health problems in the Fanteakwa districts of Ghana. Methods This community-based cross-sectional study targeted residents of the towns of the Fanteakwa districts, who have not had any dental care visit in the past six months preceding the study. The participants were enrolled from July – October, 2023. Socio-demographic study variables collected were sex, age, educational level, income level, ethnicity, area of residence, household size and frequency of brushing teeth in a day. Whereas the self-reported oral health problems were tooth ache, swollen gum, bleeding gum, sensitive tooth/teeth, hole in tooth/teeth, discoloured tooth/teeth and mouth odour. The chi-square statistical test was used to test the association between the presence of oral health problem(s) and other independent variables. Whereas, Modified Poisson regression was used to test the relationships among the variables. Results In total, 400 community members were interviewed. The mean age of respondents was 31 years (SD ± 12.4, Min = 19, Max = 81). The majority were females (55.2%) and more than 96% had some form of formal education. The Akan ethnic group accounted for as much as 47% of the respondents. The overall prevalence of self-reported oral health problems was 58.5% (95% CI 53.5% – 63.4%). The commonly reported oral health problems were toothache (51.7%), swollen gum (38.5%), difficulty in chewing (33.3%), bleeding gum (32.1%), and mobile teeth (17.1%). About 98% (229/234) of the study participants who self-reported oral health problems, reported up to four different problems. Self-reported oral health problems associated with participants’ age (χ2 = 7.2, p = 0.027), income level (χ2 = 19.3, p < 0.001), ethnicity (χ2 = 21.2, p < 0.001), area of residence (χ2 = 26.9, p < 0.001), religious affiliation (χ2 = 15.7, p < 0.001) and frequency of brushing teeth in a day (χ2 = 6.85, p < 0.032). Despite the observed relationships, Modified Poisson regression identified that compared to the rural dwellers, the urban dwellers had lower odds of self-reporting oral health problems (aOR = 0.718, p = 0.032, CI: 0.531–0.971), after controlling for age and frequency of teeth brushing in a day. Conclusion High rate of self-reported oral health problems was observed in the study site. Participants from rural residence were disproportionately affected. Therefore, local health authorities are encouraged to leverage on the identified risk groups for enhanced oral health education towards reduction in the reported oral health problems.